PERANCANGAN TROLLEY MOBILE AUDIO SEWAAN MENGGUNAKAN METODE REVERSE ENGINEERING DAN VDI 2221 - Evaprast, Barjuan Theofano; Daywin, Frans Jusuf; Gozali, Lina (Universitas Tarumanagara, 2024)
The situation after the COVID-19 pandemic made people need places for entertainment so that the tourism and entertainment sector grew rapidly. With the emergence of work from home, people need a place for entertainment. This development is in line with the quality of cafes and restaurants that need to be improved so that customers can be comfortable and repeat orders. In this process, to maintain customer retention, requests arise to hold live music, background sound, or function rooms for rent. In that case, audio is needed with good quality, easy to store, easy to adjust, move or direct so that its use can be maximized and reduce costs. Audio equipment is synonymous with large size and weight, making it difficult to move and not portable for mobile use. Therefore, a tool is needed to design a mobile audio trolley so that audio is easy to carry and use at competitive prices. With so many 4-6 inch speakers that are sold in large quantities, this is the benchmark for the dimensions of this product. By adjusting based on existing reverse engineering benchmarks known need metrics matrix, it is obtained that Product Functions in the first rank are made as priority needs. The difference after owning this product is that small equipment is safely carried around, speakers are moved easily and also with minimal effort, the speaker body remains smooth, the speaker's moisture is even more durable, it is much easier to carry and you are not afraid of the weather outside because this product is guarded.